2014
DOI: 10.1007/s11356-014-2999-0
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and copper toxicity in three marine macroalgae: evaluation of the biochemical responses and DNA damage

Abstract: Marine macroalgae have evolved a different mechanism to maintain physiological concentrations of essential metal ions and non-essential metals. The objective of the present work was to evaluate the antioxidant response and DNA damage of copper and cadmium ions in three halophytes, namely, Acanthophora spicifera, Chaetomorpha antennina, and Ulva reticulata. Accumulation of copper was significantly higher (P < 0.05) than that of cadmium. Biochemical responses showed that copper was considerably more toxic than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Elevated levels of antioxidant enzymes SOD, CAT, GR and POD in C . vulgaris following the Cd treatment in this study indicated that these enzymes could act in combination to reduce the impact of metal toxicity, the same results has reported in Acanthophora spicifera , Chaetomorpha antennina , and Ulva reticulate (Babu et al 2014 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Elevated levels of antioxidant enzymes SOD, CAT, GR and POD in C . vulgaris following the Cd treatment in this study indicated that these enzymes could act in combination to reduce the impact of metal toxicity, the same results has reported in Acanthophora spicifera , Chaetomorpha antennina , and Ulva reticulate (Babu et al 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the increased glutathione level noted in C. vulgaris when treated with Cd under 0–1 mg L −1 , that may precede phytochelatin accumulation by intracellular sequestration of metal ions (De Vos et al 1992 ). And the decreased glutathione level showed in C. vulgaris when treated with Cd under 3–7 mg L −1 , similarly, exposure of Cd decreased glutathione of A. spicifera and exposure of Cu decreased glutathione of C. antennina (Babu et al 2014 ).…”
Section: Discussionmentioning
confidence: 86%
“…With the increase of the heavy metal concentration, membrane lipid peroxidation of the algae cell wall by Zn 2+ has exceeded the repair capacity by the organism. The MDA in Ulva reticulata and Acanthophora spicifera species increased gradually with increasing concentrations of Cu and Cd (Babu et al 2014). Thus, exposure to Cu 2+ and Zn 2+ induces MDA in Cladophora.…”
Section: Effects Of Cu 2+ and Zn 2+ On The Malondialdehyde Of Cladophoramentioning
confidence: 92%
“…Cadmium toxicity also involves the binding of Cd 2? to sulfhydryl groups on critical molecules, thiol group inactivation, increased ROS levels, lipid peroxidation [3], DNA damage [4], inhibition protein synthesis [5], reduction of the activity of the antioxidant enzymes, mitochondrial damage and apoptosis [6].…”
Section: Introductionmentioning
confidence: 99%